Analysis of Benefits of the Irrigation Water Use Improvement Acceleration Program (P3-Tgai) on Improvement of Irrigation Network Infrastructure to the Regional Development at Hutagurgur Village, Regency of the Humbang Hasundutan - Friska Silitonga; Zulkifli Nasution; Agus Purwoko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The research objective is to analyze the benefits of The Irrigation Water Use Improvement Acceleration Program to improve irrigation network infrastructure, increase functional land area and increase rice productivity and increase community income for regional development in Hutagurgur Village. The location of the study was carried out in Hutagurgur Village with a sample of all P3A Gurgur Indah members as recipients of the program. Research using descriptive methods with a quantitative approach. The results showed that the Irrigation Water Use Acceleration Improvement Program had a positive effect on improving irrigation infrastructure. Evidenced by the SPSS 23 program by increasing the length of the irrigation network significantly influence the increase in the area of functional land area of 8.25 Ha. The increase in functional land has a positive effect on increasing the productivity of paddy fields, which is significantly increased by 498.45 Kg/Ha/MT and in line with the average income of farmers which increased significantly by Rp.5,172,193.42Ha/MT.